2023
DOI: 10.3390/brainsci13071116
|View full text |Cite
|
Sign up to set email alerts
|

Autism Spectrum, Hikikomori Syndrome and Internet Gaming Disorder: Is There a Link?

Abstract: The aim of this study is to review the available literature investigating the relationship between hikikomori, a pathological condition characterized by severe social withdrawal or isolation, autism spectrum disorder (ASD) and Internet gaming disorder (IGD). Studies on the relationship between ASD and IGD have found significant positive correlations between these two conditions. Individuals with ASD would appear to be at risk of developing a problematic use of the Internet, which, to the right extent, would re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…Moreover, ASD subjects are known to show marked reward dependency mechanisms and, therefore, are more easily exposed to behavioral addictions such as IGD ( 35 , 36 ). On the other hand, the use of virtual communication can be seen as an attempt of adaptative behavior that can allow ASD subjects to present a completely different personality from themselves, appearing successful and socially acceptable ( 28 , 61 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ASD subjects are known to show marked reward dependency mechanisms and, therefore, are more easily exposed to behavioral addictions such as IGD ( 35 , 36 ). On the other hand, the use of virtual communication can be seen as an attempt of adaptative behavior that can allow ASD subjects to present a completely different personality from themselves, appearing successful and socially acceptable ( 28 , 61 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…ASD is marked by enduring deficits in social communication and a consistent, repetitive display of behaviors, interests, or activities ( 15 ). It has been hypothesized that individuals with ASD, who often exhibit heightened attention to detail, weak central coherence, and sometimes specific visual skills, might possess a certain adaptability for video game tasks that demand swift visual scanning in intricate environments ( 17 ). Also, the difficulties inherent to these neuropsychiatric conditions can conceivably contribute to an appearance of the challenges presented in video games as more enjoyable, manageable, or rewarding than other tasks ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…These are associated with restricted and repetitive patterns of behavior, interests, or activities [1]. A recent review [12] found a significant association between these two conditions. The main hypotheses regarding the association between IGD and ASD evaluated the use of video games as a tool for "facilitating" relationships with peers [13], as well as the possibility that the better visuospatial abilities typically found in autistic patients make them skilled in gaming, which requires identifying numerous stimuli in complex virtual environments [14].…”
Section: Introductionmentioning
confidence: 99%
“…The main hypotheses regarding the association between IGD and ASD evaluated the use of video games as a tool for "facilitating" relationships with peers [13], as well as the possibility that the better visuospatial abilities typically found in autistic patients make them skilled in gaming, which requires identifying numerous stimuli in complex virtual environments [14]. However, many of the reported studies are based on adult patients and differences can be found in the use of standardized tests to investigate IGD [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation